Development of Robotics Learning Modules based on IoT and ESP32 - Rofi'i, Ahmad; Afianah, Nuzula; Kautsar, Syamsiar; Pratama, Aditya Wahyu; Winadi, Aditya Wahyu; Purnomo, Fendik Eko; Putri, Salsabila Liandra; Tyagita, Dicky Adi; Nari, Mochammad Irwan; Afriansyah, Faisal Lutfi (P3M Politeknik Negeri Jember, 2025)
This study aims to develop a transporter robot as a learning tool for elementary and secondary school students to introduce them to robotics. The robot features a differential drive system and a lifting arm akin to a forklift system. The robot is controlled using an ESP32 microcontroller and connected to an Android application through a Firebase cloud database. Utilizing an IoT platform, the training can be conducted online, allowing students to control the robot remotely while it remains at the training location. The transporter robot is designed to provide an interactive and hands-on learning experience in robotics, enabling students to grasp fundamental concepts in robotics, programming, and control systems. The differential drive system offers excellent maneuverability, while the lifting arm allows the robot to perform tasks such as lifting and moving objects, adding functional aspects to the learning process. Test results indicate that the robot performs well under online control, with fast and accurate responses to commands from the Android application. The use of Firebase ensures stable and real-time communication between the robot and the application. This implementation not only enhances the accessibility of robotics training but also enables the development of students' STEM skills in a more flexible and affordable manner. The study concludes that an ESP32-based transporter robot with online control via an Android application and Firebase cloud database can be an effective and innovative learning tool. This tool aims to enhance students’ STEM skills -especially in programming, control systems, and mechanical design- through interactive, real-world applications.